ANALISIS PENDAPATAN PETANI KANGKUNG DARAT(Ipomea Reptans Poir) TRADISIONAL (Studi Kasus Desa Waru Kecamatan Mranggen Kabupaten Demak Jawa Tengah) - Ridwan Ridwan; Dewi Hastuti; Rossi Prabowo (MEDIAGRO, 2014)
This study aims to determine the income of farmers Ipomea reptans, knowing Ipomea reptans Farmers' Income Level and to determine the feasibility of Ipomea reptans business. The method used in this research is descriptive analysis of samples using purposive sampling method. Research results revealed that the cultivation of kale kale Mranggen Army in Waru subdistrict, Demak ranging from land preparation to harvest Ipomea reptans. Ipomea reptans can be harvested seven times in one growing season, in one growing season lasts for four months. Cultivation swamp land by farmers in Waru still traditional. During the production season swamp land an average of 4 months, the income of farmers Rp.1.984.369 with a total area of 2402.63 m2. The average cost incurred by Rp.1.318.039,06 farmers, farmers' income by Rp.666.329,94., BEP value of farmers reached a value of BEP / breakeven in 2197 belt. so agriculture Ipomea reptans is worth the effort   Keywords : Ipomea reptans, Income, Swamp Land,